Early clinical efficacy of pegylated interferon treatment in patients with different phases of chronic HBV infection: A real‐world analysis. Issue 5 (6th January 2023) - Zhang, Wencong; Xing, Mingyou; Sun, Wenjin; Chen, Jia; Xie, Nana; Cai, Yuan; Wang, Ying; Li, Niuniu; Jiang, Yujin; Zhang, Fan; Wang, Yanfeng; Zeng, Qingjin; et al.
Abstract: Although there are therapeutic advantages for hepatitis B virus (HBV) withpegylated interferon alpha (peg‐IFNα) treatment compared with nucleos(t)ide analog (NAs) therapy, the effect difference in infected population at different phases has not been well established. We studied the clinical efficacy of peg‐IFNα in two populations with HBV infection, including inactive HBsAg carrier (IHC) and chronic hepatitis B (CHB). A total of 328 HBV‐infected patients were included in this real‐world analysis. Patients were divided into two groups according to the infected stages. Peg‐IFNα monotherapy or combination therapy with NAs were used in IHCs, and peg‐IFNα added‐on NAs therapy was applied to patients with CHB. The primary efficacy endpoint was HBsAg loss at Week 24. Results: The Kaplan–Meier cumulative rates of HBsAg loss were 39.50% ( n  = 47/119) in IHC group and 28.71% ( n  = 60/209) in CHB group at Week 24 ( p  < .05). After Propensity Score Matching (PSM), the HBsAg loss rates were 36.84% ( n  = 35/95) and 32.63% ( n  = 31/95), respectively ( p  > .05). Patients with baseline HBsAg level < 100 IU/ml achieved higher rates of HBsAg clearance in IHC and CHB group (before PSM: 47.44% vs. 42.86%, after PSM: 49.12% vs. 45.83%, all p values > .05). Baseline HBsAg level and its level decline from baseline to Week 12 can be as the predictors for HBsAg loss at Week 24 in both groups. Hence, the efficacy of HBsAg clearance was broadly similar between IHCs and NA‐treated CHB patients during the early peg‐IFNα therapy. A significant downward trend of HBsAg level was observed in both groups during peg‐IFNα therapy.